2021
DOI: 10.1093/eurheartj/ehab724.0919
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging translational approaches for accelerated clinical development of vericiguat

Abstract: Background/Introduction Vericiguat is a soluble guanylate cyclase (sGC) stimulator, like riociguat and nelociguat, and entered clinical development in 2012. Before entering Phase 2, pharmacokinetics (PK) and pharmacodynamics (PD) of vericiguat had been studied in healthy volunteers only, whereas riociguat and nelociguat had also been studied in patients with pulmonary hypertension (PH) and left ventricular dysfunction (LVD) or biventricular chronic heart failure (HF). We hypothesised that int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Data from studies of two sGC stimulators, riociguat and nelociguat, in patients with pulmonary hypertension and left ventricular dysfunction or biventricular chronic HF were available, prior to initiation of the Phase II clinical studies with vericiguat. An integrated model incorporating pharmacokinetics and hemodynamics data from riociguat, nelociguat, and vericiguat was developed to justify the appropriate dose range to be tested in the vericiguat dose-finding study SOCRATES-REDUCED in patients with HFrEF (Table 2 ) [ 59 ]. Pharmacokinetics/pharmacodynamics modeling indicated that vericiguat 2.5–10 mg would encompass an efficacious exposure range and that the 1.25-mg dose would be a “non-effective” dose level with respect to hemodynamic parameters [ 59 ].…”
Section: Pharmacokinetic/pharmacodynamic Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from studies of two sGC stimulators, riociguat and nelociguat, in patients with pulmonary hypertension and left ventricular dysfunction or biventricular chronic HF were available, prior to initiation of the Phase II clinical studies with vericiguat. An integrated model incorporating pharmacokinetics and hemodynamics data from riociguat, nelociguat, and vericiguat was developed to justify the appropriate dose range to be tested in the vericiguat dose-finding study SOCRATES-REDUCED in patients with HFrEF (Table 2 ) [ 59 ]. Pharmacokinetics/pharmacodynamics modeling indicated that vericiguat 2.5–10 mg would encompass an efficacious exposure range and that the 1.25-mg dose would be a “non-effective” dose level with respect to hemodynamic parameters [ 59 ].…”
Section: Pharmacokinetic/pharmacodynamic Relationshipsmentioning
confidence: 99%
“…An integrated model incorporating pharmacokinetics and hemodynamics data from riociguat, nelociguat, and vericiguat was developed to justify the appropriate dose range to be tested in the vericiguat dose-finding study SOCRATES-REDUCED in patients with HFrEF (Table 2 ) [ 59 ]. Pharmacokinetics/pharmacodynamics modeling indicated that vericiguat 2.5–10 mg would encompass an efficacious exposure range and that the 1.25-mg dose would be a “non-effective” dose level with respect to hemodynamic parameters [ 59 ]. These model-based approaches facilitated the accelerated development of vericiguat by avoiding the need for a proof-of-concept study in patients with HFrEF, thereby enabling immediate progression from Phase I to Phase IIb.…”
Section: Pharmacokinetic/pharmacodynamic Relationshipsmentioning
confidence: 99%